Geosites in Orava, Liptov and Spiš (N Slovakia) – evaluation, accessibility and geotouristic potential - Chrobak-Žuffová, Anna; Novotný, Jan; Michniak, Daniel (Quaestiones Geographicae, 2025)
The Sub-Tatra region, which includes Orava, Liptov, and Spiš regions, is an area with high geodiversity and biodiversity. This diversity is manifested, among others, by the occurrence of geosites of special cognitive, educational, and tourist value. This article aimed to list out such sites and their expert assessment using point valuation and triangulation methods. The authors described and assessed a total of 44 geosites, which were rock outcrops, including travertine outcrops, fragments of river valleys, lakes, caves, waterfalls, mineral water springs, peat bogs, landslides, viewpoints, and others. Of all the assessed geosites, the best values of the final valuation coefficient were obtained by the Oravské hradné bralo outcrop, the Dreveník outcrop, the Strednica viewpoint, and the Spišský hradný vrch outcrop. The authors believe that the promotion of geotourism and geosites in the Sub-Tatra region can contribute to greater dispersion of tourists and minimise the phenomenon of overtourism in the High Tatra Mts.